Musculoskeletal Interventions: A Review on Genicular Artery Embolization - Sajan, Abin; Bagla, Sandeep; Isaacson, Ari (Seminars in Interventional Radiology, 2021)
Symptomatic knee pain is one of the most common joint diseases that affects millions of people worldwide. The treatment for knee pain secondary to osteoarthritis (OA) begins with conservative therapy and progresses to surgical intervention when conservative therapy fails. Genicular artery embolization (GAE) offers an alternative option for patients who are poor surgical candidates. Multiple studies have been conducted worldwide demonstrating the safety and efficacy of GAE in patients with mild to moderate OA. The purpose of this article is to describe the current literature on GAE and highlight the latest findings from a randomized controlled trial comparing GAE versus sham embolization.
Keywords: musculoskeletal intervention; osteoarthritis; genicular artery embolization; interventional radiology